OUTBOUND DALAM PEMBELAJARAN BAHASA BALI PADA KELOMPOK BELAJAR ANAK-ANAK PENYULUH BAHASA BALI - Yasa, Putu Pertama; Mandra, I Wayan; Subagia, I Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Balinese language learning is generally carried out in three fields, namely formally, informally and non-formally. It is formally carried out at the school level starting from SD to SMA / SMK level, informally carried out in the family environment so that it is often referred to as the Mother Language, at this stage is the initial stage before the children learn formally in school. In the non-formal field, this can be done through courses which are usually carried out by certain institutions or organizations. Balinese language instructors who contribute to Balinese language learning non-formally develop methods or learning models with the concept of learning while playing, and bring learning to the surrounding environment or often called Outbound. As for the focus of this research are (1) the background of the emergence of the Balinese Language Outbound program (2) the form of the implementation of the Balinese Language Outbound (3) the implications of the implementation of the Balinese Language Outbound in the Learning group of SD Class V Balinese Language Instructors at Kalianget Village, Kec. . Seririt, Kab. Buleleng. The theories used to support this research are Behavioristic Learning Theory, Cognitive Learning Theory, Constructivism Theory.